Structural and Physico-Chemical Elucidation of Oxovanadium(IV) and Dioxouranium(VI) Complexes of N-(Pyrrolidinobenzyl)benzamide - VISWANATHAN, M. (Asian Journal of Chemistry, 2010)
Oxovanadium(IV) and dioxouranium(VI) complexes of N-(pyrrolidinobenzyl) benzamide (PBB) have been synthesized and characterized by elemental analyses, molar conductance, infrared spectra, magnetic susceptibility measurements, thermal, X-ray powder diffraction and antimicrobial studies. The complexes exhibit the following formulae [VO(PBB)2]·2H2O and [UO2(PBB)2(H2O)2].